Comparison of Sugeno and Tsukamoto Fuzzy Inference System Method for Determining Estimated Production Amount - et. al., Murnawan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the solutions to solve the problem of decision making of goods production is a decision support system to estimate the amount of production of goods using the reasoning method, Fuzzy Inference System (FIS) which is a development of the fuzzy set theory. In this study, a comparison will be made between the method Sugeno and Tsukamoto in the application of fuzzy logic to the production of goods in the company. In this research, the problem to be discussed is which method is closest to the production amount in the original data. The purpose of this study is to determine how many goods the company should produce if the variables are numbers fuzzy with calculations using the method Fuzzy Inference System Sugeno and Tsukamoto. Comparing the two results from Fuzzy Inference System Sugeno and Tsukamoto with company data. The method that comes closest to company data will be used as an application to determine the amount of production. From the calculation of the Fuzzy Inference System Sugeno and Tsukamoto, it can be concluded that the Tsukamoto method is most suitable for determining the amount of the company's goods production.